The Importance of Understanding Civil Servant Voice Behavior in Preparing to Indonesia's New Capital Relocation - Dodi Wirawan Irawanto; Khusnul Rofida Novianti; Misbahuddin Azzuhri (APMBA (Asia Pacific Management and Business Application), 2023)
The study attempts to reveal how civil servant employee voice conduct should be raised by their supervisor in order to make the relocation process of Indonesia's capital from Jakarta to Ibu Kota Nusantara (IKN)- the new name of Indonesia new capital successful. Using a qualitative approach, interpretative phenomenological analysis with an in-depth semi-structured interview is used in this study to explore in detail how participants are making sense of their personal perception regarding their movement to the IKN. The findings of this study found several important factors that are taken into consideration by civil servants in facing the relocation process to IKN, namely the support of family and partners, availability of infrastructure (accessibility to quality education, public services, transportation, and health facilities), accessibility of information, open socialization. and sustainable, as well as the role of leaders in bringing about change.